The Family - Matthijs, Koen (Sociologie Vandaag / Sociology Today, 1998)
After an academic career of 35 years, most of which as ordinary professor, Prof. Dr. Wilfried Dumon became professor emeritus at the end of September 1998. Together with a few others, he was present at the cradle of Leuven sociology in the middle of the 1960s. He participated in the construction of the necessary administrative, logistic, and academic structures as well as in the establishment of the research and educational domains in which Leuven sociology would specialize. Very soon there developed a unique sociological prespective that is known as the Leuven triangle: the integration of sociological theory, methodology, and social policy. Within this framework, the name of Wilfried Dumon is inextricably bound up with the sociology of the family, or more broadly, with the family sciences. Without doubt, he was the standard bearer of Flemish family sociology. Hundreds of students profited from his unusual - others would use much more colorful adjectives - form of teaching, in both form and content. He was directly or indirectly responsible for virtually all the courses in Leuven family sociology, also outside of his own Faculty. And those whose licentiate or doctoral thesis dealt with a theme that was in any way related to subjects like marriage, the family, or sexuality, were invariably confronted with his critical analysis and unique vocabulary. Wilfried Dumon also took on many policy positions such as editorial secretary or editor-in-chief of journals, director or manager of all sorts of institutions, and member, director or chairman of several commissions and associations. And all of this both nationally and internationally. Indeed, Wilfried Dumon had and has an extensive and tightly knit network of warm academic contacts the world over. On the occasion of his retirement, a liber amicorum has been compiled. With this initiative, the Faculty of Social Sciences, the Department of Sociology, and the Section for the Sociology of the Family, the Population and Health Care wish to express deep appreciation and gratitude for an inspirer and standard bearer. More than 20 scholars wish to give an international salute to a highly valued colleague.